Reaction of advanced inbred lines of habanero pepper to ralstonia pseudosolanacearum and phytophthora capsici - Soares, Renato S. [UNESP]; Ribeiro, Cláudia Sc; Ragassi, Carlos F; Lopes, Carlos A; Carvalho, Sabrina Ic; Reis, Ailton; Braz, Leila T. [UNESP]; Reifschneer, Francisco Jb (My University, 2019)
Habanero pepper is important in the international market and is becoming popular in the national market; however, few cultivars adapted and resistant to devastating diseases caused by the soilborne pathogens Ralstonia pseudosolanacearum (RP) and Phytophthora capsici (PC) are available in Brazil. The aim of this study was to evaluate the reaction of Habanero-type advanced inbred lines, developed by Embrapa Hortaliças breeding program, to RP and PC. Although not required for the process of protection, registration and release of new cultivars, this information is important. CNPH 15.737; CNPH 15.740; CNPH 15.744; CNPH 15.745; CNPH 15.749 and CNPH 15.750 were inoculated with three RP and one PC isolates. Plants showing wilted leaves (RP) and stem necrosis, leaf wilting and damping off (PC) were quantified. Total area under the disease progress curve (AUDPC) was obtained using incidence values and also severity index for RP. CNPH 15.740 and CNPH 15.737 were highly resistant to RP. CNPH 15.749 displayed considerable resistance levels to PC. CNPH 15.740 showed high resistance to RP isolates and intermediate resistance to PC isolates which also shows agronomic traits of interest to the sector, therefore with a high potential to be released as a new cultivar.
Reação de linhagens avançadas de pimenta Habanero a Ralstonia pseudosolanacearum e Phytophthora capsici
Keywords: Bacterial wilt; Capsicum; Incidence; Phytophthora wilt; Resistance; Severity index